Qualitative research in the ESHRE guideline ‘Routine psychosocial care in infertility and medically assisted reproduction - a guide for staff’ - Gameiro, Sofia; Wischmann, Tewes (Human reproduction, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society of Human Reproduction and Embryology. All rights reserved. For Permissions, please email: journals.permissionsoup.comSir,It was with interest that we read the invited commentary by Hammarberg et al. (2016) on how to use and evaluate qualitative research. However, we were surprised to see them expressing disappointment ‘to find that evidence from research using qualitative methods was not included in the formulation of the guidelines’, referring to the ESHRE guideline on routine psychosocial care in infertility and medically assisted reproduction (Gameiro et al., 2015). This reply intends to clarify the position of the Guideline Development Group (GDG) regarding the use of qualitative research in general and in the delineation of best practice recommendations....First, we would like to make it clear that the GDG did not a priori decide to exclude qualitative...